Perceived Relevance or Perceived Credibility: Which Factor Influences Purchase Intention Through Brand Consciousness on Tiktok? - Yana, Lisa Dwi; Nurainun; Mariyudi; Khairina (Jurnal Mebis, 2025)
This study examines the influence of perceived relevance and perceived credibility of TikTok advertising on purchase intention, with brand consciousness as a mediator. Using a quantitative approach, data were collected from 119 active TikTok users at the Faculty of Economics and Business, Malikussaleh University, through purposive sampling and analyzed using SEM-PLS. The findings revealed that both perceived relevance and perceived credibility significantly affected brand consciousness and purchase intention. Among the predictors, perceived credibility emerged as the most influential factor in shaping consumer responses to TikTok advertising. Furthermore, brand consciousness partially mediated the effects of both independent variables on purchase intention. These results underscore the importance of credible advertising content in strengthening brand consciousness and increasing purchase intention, offering meaningful academic insights into the effectiveness of digital advertising among young consumers.